Evaluation of Western blot technique for detection of antigens of Hymenolepis nana - Chávez-Salas, Flora (2007)
Enzyme-linked immunoelectrotransfer blot assay or “Western blot” was evaluated to detect specific excretory/secretory antigens from Hymenolepis nana using sera from patient with hymenolepiosis and other confirmed helminthiosis. Hymenolepis nana adults were obtained from experimentally infected golden hamster, the parasits were cultured in Minimum Essential Medium Eagle to get excretory/secretory antigens which were faced to a pool of sera from patients with confirmed hymenolepiosis to evaluate its immunological quality and with individual sera from patients with hymenolepiosis and other confirmed helminthiosis to detect by mean “Western blot” technique, this parasite specific antigens. The pool of sera from patients with confirmed hymenolepiosis recognized seven antigenic bands; 50,1; 42,6; 38.9; 26,3; 22,4; and 18,6 kDa; however, the individual sera recognized different number of bands being 50,1 kDa band the most recognized by all of them. The sera from patients with confirmed helminthiosis did not recognized 50,1 KDa band; however they gave cross reaction with some of the other bands, except the sera from patients with cysticercosis which did not recognized any of this antigen bands. Consequently 50,1 kDa antigen is specific because is recognized by all the sera from patients with confirmed hymenolepiosis and is not recognized by sera from patients with other helminthiosis using “Western blot” technique.